ANALISIS KOMPETENSI PEGAWAI DI SEKRETARIAT DAERAH KOTA CIREBON (Studi Kasus Perbedaan Kompetensi Pegawai Laki-laki dan Perempuan) - Vina Nushrotul Jannah; Ipik Permana; Moh Taufik Hidayat (Jurnal Ilmiah Publika, 2015)
ABSTRACT This Research about Competency Differences between male employees and female employees (Study Productivity of Gender).The problem is the competence of employees in Regional Secretariat of Cirebon city is not optimal, male employee competence expected to be lower than the competence of female employees.The hypothesis of the study is: "Are there differences in male employees and female employees in the Regional Secretariat of Cirebon City?"Descriptive hypothesis in the study are:H0    : there is no significant difference between male employees and female employee competence at the Regional Secretariat of Cirebon city.Ha    : there is significant difference between male employees and female employee competence at the Regional Secretariat of Cirebon city.This study uses a mixed methods research. The mixed methods research is a research that combine quantitative and qualitative research methods by mixing the methods.Results of this study was obtained from the score of respondents to variable employee competence. Male employee competencies gained percentage of 79.13%, thus the male employee competencies included in the category quite well. While the female employee competencies gained percentage of 82.13%, thus the female employee competence included in either category.The result of Independent Samples T Test using SPSS 21, obtained an average scores of male employee competence is 67.26 and an average scores of female employee competence is 69.82. It can be concluded that although the average score of competence female employees is higher than the male employees but there no significant difference because t-value of 0.175 is greater than critical t-value of 0.05 then H0 is accepted. In other words, gender did not significantly influence employee competence.